2015
DOI: 10.1136/annrheumdis-2015-eular.4550
|View full text |Cite
|
Sign up to set email alerts
|

AB1030 Juvenile Idiopathic Arthritis in Central Tunisia: Clinical and Therapeutic Features (About 54 Cases)

Abstract: BackgroundJuvenile idiopathic arthritis (JIA) groups several entities having in common the presence of arthritis that begin before the age of 16, persist for more than six weeks and have no identified cause.ObjectivesThe aim of our study was to determine the feature of the different clinical forms of JIA.MethodsThis is a retrospective study of 54 cases of JIA according to the criteria of the International League Association of Rheumatology in department of Rheumatology collected over a period of 16 years [1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Unlike similar studies published in Oman and Tunisia where Polyarticular JIA is the most common subtype 46.7%, 66% respectively (11,12) , whereas systemic juvenile arthritis (36.5%) was the most common subtype in another study from Saudi Arabia (13) . Table 6 summarizes the published data on JIA patterns in different countries.…”
Section: Discussioncontrasting
confidence: 67%
“…Unlike similar studies published in Oman and Tunisia where Polyarticular JIA is the most common subtype 46.7%, 66% respectively (11,12) , whereas systemic juvenile arthritis (36.5%) was the most common subtype in another study from Saudi Arabia (13) . Table 6 summarizes the published data on JIA patterns in different countries.…”
Section: Discussioncontrasting
confidence: 67%
“…With regard to published data from some countries in the Middle East and North Africa (MENA), such as Lebanon (31%), Iraq (48%), Saudi Arabia (40.5%), and Egypt (41.3%), oligoarticular JIA was the most common subtype (7,8,9,10) . Whereas other reports from MENA found polyarticular JIA to be the most common subtype in Oman (46.7%) (11) and Tunisia (66%) (12) . We compared our data in this study with those from countries in MENA and other regions, as shown in Table 8.…”
Section: Discussionmentioning
confidence: 65%
“…With regard to published data from some countries in the Middle East and North Africa (MENA), such as Lebanon (31%), Iraq (48%), Saudi Arabia (40.5%), and Egypt (41.3%), oligoarticular JIA was the most common subtype [ 4 7 ]. Whereas other reports from MENA found polyarticular JIA to be the most common subtype in Oman (46.7%) [ 8 ] and Tunisia (66%) [ 9 ].…”
Section: Discussionmentioning
confidence: 95%